Svetosavlje — omen for numen orthodoxy - Грбић, Јелена М (Sabornost - The Theological Year-book, 2013)
Svetosavlje as a phenomenon emerging from Milesevo cult of Saint Sava, and it means mentality, folk and historical component of the Serbs in a wide spectrum of ecumenical orthodoxy. Although a Serbian мiddle аges elapsed in that spirit, term did not exist. It occured in areas of the Sava and Danube in the festivities which the Serbian people celebrating the memory of the first Serbian archbishop and their spiritual father. First was created compound adjective, and only a ten years before World War II the noun svetosavlje. This paper attempts to examine the essence of the svetosavlje as an unique phenomenon in the history of Christianity. This paper discusses the genesis of the concept of svetosavlje and its various interpretations that often occur as a result of reducing the saintly figures of the first Serbian archbishop. It also makes a comparison of two different concepts of the enlightenment: illumination of St. Sava and the 18th century englightenment. At the end, the paper strives to finde out what the life philosophy of svetosavlje and phrase roud of svetosavlje means.